The audit expectations gap: mitigating information asymmetries and corporate social responsibility as a signaling device - Ojo, Marianne; Ali, Azham; Lee, Teck Heang; Mohamad, Rosli; Mohamad Yusof, Nor Zalina (IGI Global, 2016)
Corporate Social Responsibility necessitates effective engagement of stakeholders and investors – both at local and international levels. As well as demonstrating that changes in perceptions do not warrant an internship program as a means of reducing the audit expectations gap as misperceptions are still found among respondents on issues of auditing after the completion of the internship program, this chapter will seek to demonstrate why Corporate Social Responsibility endeavors which focus on the mitigation of information asymmetries between the management of an enterprise and local and international investors, also translates to effective corporate social responsibility reporting – in the sense that the engagement of stakeholders - facilitated primarily through legal and ethical responsibilities, ultimately results in the realization of economic and philanthropic responsibilities.From an economic perspective, the mitigation of information asymmetries and systemic risks, without doubt, constitutes the most important of rationales or other objectives that could be presented.